(untitled) (De Musica, 2024)
In analyzing Wittgenstein’s music aesthetics, various authors have pointed out the resemblance between Wittgenstein’s view and Hanslick’s writings on musical formalism. The similarities between the two can be found especially in two areas: in the role attributed to the structural characteristics of the musical work, used to highlight interesting facts for the listener, and in the strong refusal of a reductionist interpretation of music, according to which the essence of music consists in generating specifics emotions in the audience. However, there are also some remarking differences between the two authors, especially in the second phase of Wittgenstein’s philosophical work, which is centered on emotional and non-grammatical aspects of human forms of communication. In this paper, the critical views of Béla Szabados and Anne Appelqvist are compared, to show how difficult it can be to fit what Wittgenstein wrote about music in one simple box. A difficulty that was also pointed out by other authors, such as Roger Scruton and Alessandro Bertinetto, who both abandon the classical dichotomy between musical formalism and anti-formalism, to better focus on the peculiarities of Wittgenstein’s work.